Functional Analysis of the Verbal Interaction Between Psychologist and Client During the Therapeutic Process. (July 2013) - Ruiz-Sancho, Elena M.; Froján-Parga, María Xesús; Calero-Elvira, Ana
The goal of this study is to analyze the verbal interaction that takes place between client and therapist over the course of a clinical intervention so as to analyze the potential learning processes that may be responsible for changes in the client's behavior. A total of 92 sessions were analyzed, corresponding to 19 clinical cases treated by 9 therapists specializing in behavioral therapy. The variables considered were therapist and client verbal behaviors, and these were categorized according to their possible functions and/or morphologies. The Observer XT software was used as a tool for the observational analysis. The results led to the conclusion that the therapist responds differentially to client verbalizations, modifying the verbal contingencies as his or her client content approaches or becomes more distant from therapeutic objectives. These results suggest the possible existence of verbal "shaping" processes through which the therapist guides the client's verbal behavior toward more adaptive forms. In addition, this study proposes an alternative to the traditional controversy regarding the relevance of the therapeutic relationship versus the treatment techniques used to explain clinical change. This article suggests that such differentiation is unnecessary because the therapeutic relationship and the treatment techniques should act in the same manner, this is, in providing the context for the occurrence of what is truly therapeutic, namely, the learning processes.